2020
DOI: 10.11591/eei.v9i5.2238
|View full text |Cite
|
Sign up to set email alerts
|

Wideband millimeter-wave substrate integrated waveguide cavity-backed antenna for satellites communications

Abstract: This paper presents a new type of wideband waveguide (SIW) cavity-backed patch antenna for millimeter wave (mmW). The antenna proposed applies to applications of 31-36 GHz Ka-band such as satellites communications. The SIW is intended with settings for particular slots. The antenna is constructed on Rogers RT5880 (lossy) with 2.2 dielectric constant, l.27 mm thickness, and 0.0009 loss tangent. It is simulated in the programming of computer simulation technology (CST) Microwave Studio. The simulated results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…It also achieved an efficiency of 80% and a gain of 8.87 dBi. This means that the antenna will work properly on the desired application [8]. Since the study utilized a cavity for their antenna, it showed that there are changes with regards to functions of the antenna.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…It also achieved an efficiency of 80% and a gain of 8.87 dBi. This means that the antenna will work properly on the desired application [8]. Since the study utilized a cavity for their antenna, it showed that there are changes with regards to functions of the antenna.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…The microstrip patch basically have four part which is patch, ground, substrate ad feeding part. The advantage of the microstrip patch it has small size, low profile and lightweight conformable to planar and non-planar surface [6]. The objectives of this project are to design a compact antenna for 5G.…”
Section: Introductionmentioning
confidence: 99%